Bridging the Gap: Socio-Economic Factors in the Implementation of Rusunawa and Kotaku Housing Policies in Indonesian Low-Income Communities - Siti Zubaidah; Deden Hadi Kushendar; Jumroh Jumroh; Siti Waliah; Hermansyah Hermansyah; Cifebrima Suyastri (Dealings Foundation Institute, 2026)
Housing implementation often overlooks socio-economic factors, which are crucial for ensuring inclusivity among Low-Income Communities (LICs). This study addresses this gap by measuring the influence of socio-economic variables in the management of public rental housing (Rusunawa) in Cimahi and slum upgrading programs (Kotaku) in Palembang, Indonesia. Employing a sequential mixed-methods design (QUAN → QUAL), 500 tenants were surveyed to assess employment stability, household income, financial accessibility, and housing affordability. Follow-up interviews and focus group discussions were conducted with 30 policymakers, administrators, and tenants to explore qualitative perspectives. The findings reveal that socio-economic factors significantly influence rent payment consistency, tenancy security, and overall housing policy effectiveness. To improve policy effectiveness, the study recommends integrating socio-economic assessments into housing policy design, such as implementing income-based rental adjustments, providing targeted financial support for informal sector workers, and improving access to financial services for low-income tenants. These changes would promote greater inclusivity, long-term sustainability, and social equity within housing programs.